Perancangan Sistem Kendali pada Periode Waktu untuk Lansia Menggunakan Sepeda Statis - Nabilah Hanun; Farida Arinie Soelistyanto; Rachmad Saptono (Jurnal Jaringan Telekomunikasi, 2021)
The average senior spends his time indoors also needs enough exercise, so a static bike is needed that can display heart rate and body temperature data while exercising, so that further action can be taken after knowing the measurement results. On static bikes there are Heart Rate sensors, DS18B20 temperature sensors, and Infrared FC-51 sensors as detectors for the number of laps and wheel speeds. When the elderly start cycling with the selected duration and the photodiode sensor detects the presence of rotation then the Heart Rate sensor and DS18B20 sensor will be able to display heart rate and body temperature data. Data from sensors during cycling is transmitted wirelessly via NodeMCU so that it can be displayed in the android app until the time runs out and the alarm will sound, from the data obtained can result in a normal or abnormal diagnosis of heart rate and body temperature values. In addition, it can also be known the quality of body temperature and heart rate based on the number of rounds and the speed of the wheel. From the results of the study can be concluded that the determination of normal diagnosis in the elderly when the body temperature ranges from 35°C - 38°C and the heart rate can be calculated by a formula that is 220 minus age. During the process of sending data obtained average – troughput average of 9 tests of 6,153 Kb/s with a minimum delay of 28,590 ms and maximal of 88,078 ms.